건강 관련 커뮤니티 시설 특성 유형화 및 거래가격과의 관계 - 최원준(Won-Joon Choi) (한국콘텐츠학회 논문지, 22(8), 2022)
Recently, 'Apartment community facilities' have emerged as the most optional factor in the apartment market, and their level is becoming very important. Therefore, this study derived each type through latent profile analysis centering on health-related community facilities in 126 domestic main apartment complexes, and as a result of the analysis, it was confirmed that it was divided into a Pilates group, GX and Yoga group, Golf and Table Tennis practice range group, and overall low group. Among the four groups, Pilates, GX, and yoga groups are more likely to belong to Gangnam, Seocho and Songpa compared to complexes with many golf and table tennis practice ranges, and at the same time, the transaction price is also the highest. Through these analysis results, it was suggested that changes in the preference for leisure activities should be reflected when constructing community facilities, and that health-related community facilities should be deeply considered in residential welfare policies in consideration of high preference for fitness facilities in youth housing. 최근 아파트 시장에서 가장 많은 선택 요인으로 부각되고 있는 것이 '아파트 커뮤니티 시설'이며 그 수준이 매우 중요해지고 있다. 이에 본 연구는 국내 주요 아파트 단지 300세대 이상, 126곳을 대상으로 건강 관련 커뮤니티 시설을 중심으로 잠재 프로파일 분석을 통해 각 유형을 도출하였으며, 분석 결과 필라테스 집단, GX 및 요가집단, 골프 및 탁구연습장 집단, 전반적 저집단 총 4집단으로 구분됨을 확인하였다. 4집단 중 필라테스 집단과 GX 및 요가집단은 골프 및 탁구연습장이 많은 단지에 비해 강남, 서초, 송파 등에 속할 가능성이 높음과 동시에 거래가격 역시 가장 높은 것으로 분석되었다. 이러한 분석결과를 통해 커뮤니티 시설을 구성할 때 여가활동 선호의 시대적 변화를 반영해야 한다는 점, 청년주택 등에서의 피트니스 시설에 대한 높은 선호도를 감안하여 주거복지정책에서도 건강 관련 커뮤니티 시설 제공 계획을 깊게 고려해야 한다는 점 등을 제언하였다.